Optimization of hydrolysis time for food protein hydrolysate from food waste (fish, shrimp & okara): article - Zulkifly, Nur Izzati Syamimi; Tan, Huey Ling (2019)
Every year, a huge amount of food waste such as fish, shrimp and soybean waste are generated by their food processing industries. Fish, shrimp and soybean (okara) waste such as skin, head, tail fins, and shell are being discarded or simply dumped without further processing. The aim of this study was to extract the bioactive peptide from food waste by using enzymatic hydrolysis and to optimize the hydrolysis time for food waste from fish, shrimp and okara by variable time constraint between 2 until 5 h with 1 hr interval. Enzymatic hydrolysis of proteins was carried out using alcalase enzyme at 2 % (w of enzyme/ w of substrate), 60 ℃ at four hydrolysis times (2, 3, 4, and 5 h).The food waste (fish, shrimp and okara) was blended using a Mastar blender to obtain the slurry types of sample. The highest degree of hydrolysis (DH) for fish, shrimp and okara are at 2% enzyme concentration, 60 ℃ after 4 h of hydrolysis. The protein determination and analysis were determined by using several laboratory equipments such as UV-Vis Spectrometer, and Fourier Transform Infrared (FTIR) Spectroscopy.